Effects of nitrogen fertilizer on root-shoot characteristics, grain yield and nitrogen use efficiency of different maize varieties in North China Plain - Li, Xiangling; Liu, Pan; Wang, Rui; Zuo, Yiping; Wang, Jian; Han, Jinling; Zhang, Yuechen; Yin, Baozhong (International Journal of Agricultural and Biological Engineering, 2022)
Excessive nitrogen (N) fertilizer application in crop production has resulted in a series of environmental issues in North China Plain (NCP). Breeding N-efficient maize varieties is one of the effective strategies to improve the N use efficiency of maize and reduce environmental pollution. This study designed an experiment for two maize varieties (‘Xian-Yu 335’ [XY335] and ‘Hua-Nong 138’ [HN138]) with three N-level treatments (0 kg/hm2, 180 kg/hm2, 300 kg/hm2, i.e. N0, N180, N300). The aim of the study was to determine the response characteristics of maize canopy structure, root morphology, and anatomical structure, as well as N uptake and utilization of N fertilizer. Results showed that grain yield, N use efficiency, and N harvest index of XY335 were higher 5.20%-13.68%, 11.86%-19.11%, and 6.07%-3.33% than those of HN138, respectively. Compared with HN138, XY335 had a higher leaf area index and photosynthetic nitrogen-use efficiency. The root length, root length density, root absorption area, root absorption area, and root active absorption area of XY335 in each period were higher than that of HN138. The proportion of RCA of XY335 was significantly higher than that of HN138, which was 14.64% higher on average. In the future breeding process, the high N and low N double-high-efficiency varieties should pay more attention to the improvement of root cortex aeration tissue. Keywords: maize, root, nitrogen accumulation, nitrogen use efficiency, yield DOI: 10.25165/j.ijabe.20221505.6694 Citation: Li X L, Liu P, Wang R, Zuo Y P, Wang J, Han J L, et al. Effects of nitrogen fertilizer on root-shoot characteristics, grain yield and nitrogen use efficiency of different maize varieties in North China Plain. Int J Agric & Biol Eng, 2022; 15(5): 132–140.